The Morphosyntax of Magahi Addressee Agreement. (25th April 2021) - Alok, Deepak
Abstract: This article analyzes addressee agreement (allocutive agreement) in Magahi, an Eastern Indo‐Aryan language. Magahi finite verbs encode the honorificity (social status) of the addressee, in addition to encoding the person and honorificity of the subject. Magahi addressee agreement is special in two respects. First, it is associated with finiteness: it is available in all finite clauses, main and embedded. Second, addressee agreement and subject honorification combine features for spellout, indicating that heads involved in both phenomena are syntactically adjacent. I claim that the covert syntactically expressed representation of the addressee, which undergoes addressee agreement, is relatively low in the clause structure: it is a coordinate of FinP, the layer just above TP. I further propose that the functional head associated with Magahi addressee agreement is the Fin head. The proposal diverges from previous analyses, in which the locus of addressee agreement is the highest projection of a clause (Speech Act Phrase or Context Phrase), found primarily in root clauses. This study implies that the addressee is syntactically present in every finite clause. Crosslinguistic differences (e.g., root–embedded asymmetries) depend on what syntactic category acts as a probe in a language.